2016
DOI: 10.7861/clinmedicine.16-6-s79
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pills and tests: addressing the social determinants of tuberculosis

Abstract: Poverty drives tuberculosis (TB) rates but the approach to TB control has been disproportionately biomedical. In 2015, the World Health Organization's End TB Strategy explicitly identified the need to address the social determinants of TB through socio-economic interventions. However, evidence concerning poverty reduction and cost mitigation strategies is limited. The research described in this article, based on the 2016 Royal College of Physicians Linacre Lecture, aimed to address this knowledge gap. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 60 publications
1
48
0
1
Order By: Relevance
“…In the current study, the majority (84.7%) of the cases had visited an average of 2.2 HCFs until diagnosis of TB at which time both self and prescribed medicines had been used. Third, delays to treatment often accompanied by higher direct and indirect costs that impoverish households [ 36 , 37 ] and ultimately lead to poor treatment compliance and outcome [ 36 ]. In our study we observed significantly higher median pre diagnosis (US$119.1 vs 48.2, p = 0.001)and post diagnosis (US$93.7vs.98.8, p < 0.001) costs among those delayed to initiate treatment which could explain the increased risk of unsuccessful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the majority (84.7%) of the cases had visited an average of 2.2 HCFs until diagnosis of TB at which time both self and prescribed medicines had been used. Third, delays to treatment often accompanied by higher direct and indirect costs that impoverish households [ 36 , 37 ] and ultimately lead to poor treatment compliance and outcome [ 36 ]. In our study we observed significantly higher median pre diagnosis (US$119.1 vs 48.2, p = 0.001)and post diagnosis (US$93.7vs.98.8, p < 0.001) costs among those delayed to initiate treatment which could explain the increased risk of unsuccessful outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The average expenditure incurred by patients in low-income and middle-income countries towards diagnosis and treatment of TB ranges from $55 to $8198,1 placing their households at higher risk of catastrophic costs due to TB care 2–6. Catastrophic costs create access and adherence barriers, which, in turn, are associated with adverse TB treatment outcomes including death, failure of treatment, loss to follow-up, recurrence and multidrug-resistant (MDR) TB 7…”
Section: Introductionmentioning
confidence: 99%
“…La tuberculosis (TB) es una enfermedad infectocontagiosa, prevenible, curable y con un importante componente social (1) . Según estimaciones de la Organización Mundial de la Salud (OMS), la incidencia anual de la TB a nivel mundial está disminuyendo lentamente, alrededor de 1,5% desde el año 2000; sin embargo, el número absoluto de casos de TB se viene incrementando.…”
Section: Introductionunclassified